Educational Views of Ibn Hajar Al-Haytami Through his Book (Editing the Article on Etiquette, Rulings and Benefits Needed by Children's Educators): - Alsorayai, Khulood Hamdan (Journal of Educational and Psychological Sciences, 2022)
The current research aims to identify the educational views of Ibn Hajar Al-Haytami through his book “Editing the Article on Etiquette, Rulings and Benefits Needed by Children's Educators” with a brief overview of his life, age, and scientific status, the most important of his Sheikhs and students who studied under him, his most famous scientific works, and clarification of his educational approach through endowment. Education, the process of learning and teaching children, and the educational curriculum that he drew in his book, including objectives, content, and educational teaching methods. The researcher has adopted the descriptive analytical approach, the researcher also found the most important patterns of the executive management process in the endowment house according to Ibn Hajar Al-Haytami, explaining the roles of the endowment owner, the principal, the teacher and the learner and highlighting the role of the teacher in the educational process and the nature of the relationship between the teacher and the learner. The researcher recommends the necessity of making endowments and paying attention to them to support education, universities and scientific research, not limiting them to certain areas such as mosques and digging wells, researchers should conduct more studies in children’s literature in the light of Islamic education for advanced scholars and benefit from them in contemporary society.
Keywords: Views; Ibn Hajar Al-Haytami; Education; Endowment